Corruption and Companies: The Use of Facilitating Payments - Argandoña, Antonio (Journal of business ethics, 2005)
Making use of facilitating payments is a very widespread form of corruption. These consist of small payments or gifts made to a person – generally a public official or an employee of a private company – to obtain a favour, such as expediting an administrative process; obtaining a permit, licence or service; or avoiding an abuse of power. Unlike the worst forms of corruption, facilitating payments do not usually involve an outright injustice on the part of the payer as they are entitled to what they request. This may be why public opinion tends to condone such payments; often they are assumed to be unavoidable and are excused on the grounds of low wages and lack of professionalism among public officials and disorganisation in government offices. Many companies that take the fight against “grand” corruption very seriously are inclined to overlook these “petty” transgressions, which are seen as the grease that makes the wheels of the bureaucratic machine turn more smoothly. Despite this, facilitating payments have a pernicious effect on the working of public and private administrations: all too often they are the slippery slope to more serious forms of corruption; they impose additional costs on companies and citizens; and in the long run they sap the ethical foundations of organisations. Although many articles on corruption mention facilitating payments, there have been no systematic studies from a company’s point of view. This article thus focuses on facilitating payments from the point of view of the company that makes the payment, either as the active partner (when it is the company that takes the initiative) or as the passive partner (when the official or employee is the instigator).